IMPLEMENTASI ETIKA ISLAM DALAM BERBISNIS - Holle, Mohammad H (AMAL: Jurnal Ekonomi Syariah, 2019)
This paper aims to uncover the ethical values of Islam contained in business activities. Good or bad behavior is a reflection of human life, both individually and in groups. This behavior is also commonly found in business activities. The purpose of doing business is to make a profit. But sometimes the desire to cover up human reason and do losses by doing business. The basic law of doing business in Islam is permissible, unless there is a prohibition from Allah. A number of prohibited acts in doing business such as; take usury, cheat, reduce the scale, hoard merchandise, take the property of others, monopoly, betrayal, perjury, and speculation. In Islam, a number of ethics that we usually encounter in business include; stay away from business goods or illicit activities, stay away from the element of fraud, buying and selling halal, fair, honesty, keep promises, write transactions that are not cash, agree, leave the business when prayer times and pay zakat arrives. In Islamic ethics it does not invite an entrepreneur just to pursue profit, but a blessing. That the benefits are reasonable and not excessive. Business benefits according to Islam are not only material but also immaterial. Business is also not only a container associated with humans alone but also related to Allah. As a number of the words of Allah contained in QS an-Nissa (4): 29, al-Baqarah (2): 282; at-Taubah (9): 24; an-Nuur (24): 37; Fatir (35): 29; al-Saff (61): 10, and al-Jumu'ah (62): 11. Keywords: implementation, ethics, Islam, Business